Recuperação de informação em plataformas de audiolivros: recomendações para metadados e funcionalidades - Suellen Souza Gonçalves (2024)
The audiobook is an informational resource that allows you to listen to narrative, academic, scientific, didactic, literary works, among other contents that encompass a great diversity of data and information, covering various textual and literary genres, being an audio version of a book. As an informational resource, the audiobook has undergone changes with technological progress and, therefore, to represent and retrieve the information contained therein, ensuring its use and efficient access to users, new formats and standards are necessary. In the same direction, information retrieval, which deals with different types, formats and items of information, needs to be aligned with the audiobook, in order to provide quick and relevant access to users' informational needs in new digital environments. The general objective of this dissertation was to develop recommendations for information retrieval on audiobook platforms in the Brazilian context. As specific objectives, we sought to (1) identify and map studies on the topic of audiobooks in the area of Information Science, (2) identify and map the resources of audiobook platforms available in Brazil, (3) analyze the resources, functionalities and forms of representation and retrieval of information on audiobook platforms and (4) systematize the results and develop recommendations to support the retrieval of information on these platforms. Methodologically, the research was characterized as exploratory, descriptive and applied, with a qualitative and quantitative approach, divided into four stages, one for each specific objective. The results were presented according to the stages and in the first, after mapping the studies on the topic, gaps were identified in relation to the representation and retrieval of information on audiobook platforms. In the second stage, the nationwide opinion survey provided information on users' perception and behavior, as well as identifying the most used platforms in the Brazilian scenario: Audible, Ubook, Skeelo, Storytel and Tocalivros. In the third stage, the analysis of metadata and functionalities in mobile and desktop environments revealed that the Audible platform stood out, meeting 69% of all analyzed criteria. Finally, in the fourth stage, based on the systematization of the results of the previous stages, the recommendations developed for information retrieval on the platforms suggested: standardizing metadata, standardizing resources and functionalities between mobile and desktop environments, implementing advanced searches, using techniques such as: machine learning, conversational artificial intelligence, among others. It was concluded that the recommendations can be used in new projects and standards involving audiobooks, mainly to improve existing platforms, highlighting the importance of Information Science for organization and recovery in digital environments. As future work, new research on related topics is suggested, such as indexing techniques for audiobooks, interoperability standards, usability and accessibility on platforms.